Influence of Management Factors on Social Economic Performance of Entrepreneurship Groups in Pumwani Informal Settlements in Nairobi County, Kenya - Mbogo, Patricia Njeri; Matheka, Dr. Veronicah M. (International Journal of Entrepreneurship and Project Management, 2016)
Purpose: The purpose of this research was to analyze the influence of management factors on social economic performance of social entrepreneurship groups of Pumwani informal settlements in Nairobi County. Methodology: This study was quantitative in nature and employed a descriptive research design. The target population was 980 members of the 50 registered self-help groups within Pumwani. The study used simple random sampling select 130 members in total who shall be the respondent of the research questionnaire. The study used primary data collected using a 5 point Likert scale questionnaire. Validity of research instrument was established through the help of the Supervisor who is an expert in the field. The supervisor scrutinized the items for relevance in relation to the topic. A pilot test was conducted to test the reliability of the research instrument. Descriptive statistics were used to analyze the data. The results were presented in form of tables. Results: Result findings indicated that there is a positive and significant relationship between financial management, capacity building, monitoring and evaluation and stakeholder management and socio economic performance of socio entrepreneurship groups Unique contribution to theory, practice and policy: Based on the study findings this study recommended that leaders of socio entrepreneurship groups in slums should encourage more people to join these groups as this would help in achieving the medium term goal of the vision 2030 of poverty eradication. The study also recommended that the leadership of the socio entrepreneurship groups should encourage the members to work in groups so that they can share ideas and come up with unique and profitable business ventures.